Tagore and Yeats : a postcolonial re-envisioning - Brewer Redwine, Elizabeth (Cross/cultures, 2022)
The Yeats-Tagore friendship and the eventual curious fallout between the two remain a mystery; the focus of this volume is a postcolonial reading of the two writers' friendship, the critical reception of Tagore in 1912 England, and Tagore's erasure from Western literary discourse. The essays in this volume take a decolonial turn to critically analyze the two writers in the discourse of power that is a part of their larger story.